Motivation and Learning Outcomes after Using PhET Simulations on Hydrostatic Pressure: A Quantitative Analysis - Fhazriani Riau; Indri Sari Utami; Annisa Shafirah; Siti Khoirunisa; Helsa Putri Pratama; Novita Ayu Permata Sari; Ridwan Ridwan; Muhammad Yusrizal (Universitas Muhammadiyah Cirebon, 2025)
This article examines the relationship between learning motivation and physics learning outcomes on hydrostatic pressure material after the use of PhET simulation media in grade XI students at SMAN 1 Petir, Banten. The study used a quantitative approach with a descriptive-correlational design involving 22 purposively selected students. Research instruments included a Likert-scale learning motivation questionnaire, multiple-choice tests, and semi-structured interviews to strengthen interpretation. The results show that students’ motivation is in the good category, while learning outcomes are very high and homogeneous, with 86.36% of students achieving a perfect score, creating a ceiling effect that reduces variability. Spearman correlation analysis yielded a coefficient of –0.23, indicating a very weak and insignificant negative relationship between motivation and learning outcomes, suggesting that motivation is not a key predictor of academic performance in this case. The findings point to the influence of other factors such as cognitive abilities, learning strategies, and test characteristics that better explain learning performance. Researchers recommend improving evaluation instruments to increase sensitivity, adding moderating variables such as self-regulated learning or self-concept, and using mixed methods for a more comprehensive understanding of the relationship between motivation and learning outcomes in science education.